The lost art of caring : a challenge to health professionals, families, communities, and society - Cluff, Leighton E.; Binstock, Robert H. (Johns Hopkins University Press, 2001)
In this book, clinician Cluff and social scientist Binstock bring together experts to address the importance of caring, the reasons why it has eroded, and measures that can strengthen caring as provided by health professionals, families, communities, and society.--From publisher description.